The dermatoses of pregnancy - Sachdeva Silonie (Wolters Kluwer Medknow Publications, 2008)
The skin changes in pregnancy can be either physiological (hormonal), changes in pre-existing skin diseases or development of new pregnancy specific dermatoses. Pregnancy-specific skin dermatoses include an ill-defined heterogeneous group of pruritic skin eruptions which are seen only in pregnancy. These include atopic eruption of pregnancy, polymorphic eruption of pregnancy, pemphigoid gestationis and intrahepatic cholestasis of pregnancy. Atopic eruption of pregnancy is the most common of these disorders. Most skin eruptions resolve postpartum and require only symptomatic treatment. Antepartum surveillance is recommended for patients with pemphigoid gestationis and intrahepatic cholestasis of pregnancy as they carry fetal risk. This article deals with the classification, clinical features and treatment of the specific dermatoses of pregnancy.